2003
DOI: 10.1002/er.903
|View full text |Cite
|
Sign up to set email alerts
|

Refrigeration plant exergetic analysis varying the compressor capacity

Abstract: The paper presents an exergetic analysis of a vapour compressor refrigeration plant when the refrigeration capacity is controlled by varying the compressor speed. The aim is performance evaluation of both the whole plant and its individual components. The analysis of the exergy flow destroyed in each device of the plant varying the compressor speed has been carried out in order to determine the relative irreversibility of the plant components. The vapour compression plant is subjected to a commercially availab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 6 publications
1
24
0
Order By: Relevance
“…Taking a short review on the previous studies, similar results for the exergy analysis were reported [6,9,23]. Additionally, Aprea and Renno [9] have used semi-hermetic compressor in their variable-speed experimental refrigeration cycle and found that the irreversibility rates were 37% at the compressor, 27% at the condenser, 23% at the evaporator and 13% at the expansion valve using R407c as the working fluid.…”
Section: Resultssupporting
confidence: 55%
“…Taking a short review on the previous studies, similar results for the exergy analysis were reported [6,9,23]. Additionally, Aprea and Renno [9] have used semi-hermetic compressor in their variable-speed experimental refrigeration cycle and found that the irreversibility rates were 37% at the compressor, 27% at the condenser, 23% at the evaporator and 13% at the expansion valve using R407c as the working fluid.…”
Section: Resultssupporting
confidence: 55%
“…This uncertainty together with the medium value considered for ðeCÞ co influences the calculation of the evaporation temperature, the refrigerant mass flow rate and the COP. Also, the uncertainty linked to the compressor efficiency determination involves the discrepancy existing between the COP values determined both experimentally and by means of the model; in particular, the compressor efficiency is provided with an uncertainty equal to AE 1.1% (Tassou and Quereshi, 1998;Aprea et al, 2003). With respect to the refrigeration power the uncertainty is equal to AE 0.4%, while as for the air temperatures at the evaporator and the condenser though more thermoresistances have been used to measure the temperature, an uncertainty exists because the experimental plant does not present channels suitable in length for a correct air temperature measurement.…”
Section: Resultsmentioning
confidence: 99%
“…Similar considerations are assumed for the compressor efficiency whose value at 50 Hz is about 0.7 and its trend is also linear when the compressor speed varies (Tassaou and Quereshi, 1998;Aprea et al, 2003). As for the refrigeration capacity, it is possible to determine its value also for other frequencies determining by means of a catalogue its value at 50 Hz and knowing experimentally (Tassou and Quereshi, 1998;Aprea et al, 2003) that it decreases linearly by about 20% at 30 Hz. It is possible to determine its value for other frequencies also.…”
Section: Model Descriptionmentioning
confidence: 94%
See 2 more Smart Citations